Transnational Mobility and Global Health - Koehn, Peter H., author.
1 online resource (280 pages)
Keywords: Transnational Mobility and Global Health spotlights the powerful and dynamic intersections of human movement, inequality, and health. The book explores the interacting political, economic, social, cultural, and climatic drivers of health and migration, proposing innovative ways to enhance global health and care provision in an era of transnational mobility. As health security continues to rise up the agenda in international politics, the book also analyses the political determinants of health and migration.Within the framework of key drivers of unequal mobilities, this book treats interconnected health and migration themes not covered elsewhere under one cover: health tourism, conflict-induced and other vulnerable-population movements, humanitarian crises, human rights, the health-development linkage, migrant health-care, and health-competency education. The book also considers global health vulnerabilities in the wake of climate change, and the biomedical, ethical, and governance challenges of emerging and reemerging infectious diseases. Finally, the book suggests ways of evaluating mobility-influenced health outcomes and equity impacts, and explores how the global circulation of health expertise could help to rectify care-provider shortages.The challenges to global health considered in this book are only likely to become more intense as the 21st-Century surge in transnational migration continues. Readers will gain interdisciplinary appreciation for the relevance of health for migration and of migration for global health. Researchers, students, practitioners, and policy makers interested in individual and population health, sustainable development, and migration studies will find this book a useful and inspiring guide to contemporary global challenges.